SISTEM PENDIDIKAN ISLAM DI MADRASAH MUHAMMAD BASIUNI IMRAN SAMBAS - Nurhalimah , Nurhalimah (ILJ: Islamic Learning Journal, 2023)
Islamic education is carried out in a system, namely the Islamic education system. The Islamic education system is carried out optimally if the educational components can run as they should and have cooperation and are continuous between one component and the other in achieving the goals of Islamic education. The Islamic education system of each school or madrasah is different so that the resulting impact is also different. The research method used in this study is literature, field studies (observing) and documents. The data collection method used was to collect reviews of books, journals and other literature to be analyzed according to the focus of this study. The results state that the Islamic education system at Madrasah M. Basiuni Imran Sambas is open, namely a system with a structure with components that are adaptable and easy to adjust to various changes that occur in each component of Islamic education.